The Role of Laparoscopy in Modern Gynecology: Advancements, Applications, and Clinical Outcomes - Sarin, Devishi; Memon, Hina Nisar Ahmed; Sughra, Ghulam; Kousar , Shermeen; Elrasheed, Fath Elrahman; Nadeem, Habibah; Siddiqui, Sobia Naseem (Indus Journal of Bioscience Research, 2025)
This study explores the role of laparoscopy in modern gynecology, focusing on its advancements, applications, and clinical outcomes. Laparoscopy has revolutionized gynecological surgeries by providing a minimally invasive approach that improves recovery time, reduces postoperative pain, and enhances cosmetic outcomes compared to traditional open surgeries. A total of 110 patients undergoing either laparoscopic or traditional open surgeries for various gynecological conditions were included in this study. The methodology involved a comparative analysis of recovery time, postoperative pain, and cosmetic outcomes between the two groups. Statistical analyses, including paired t-tests and ANOVA, were performed to identify significant differences. The results revealed that laparoscopic surgery significantly reduced recovery time (3.5 ± 1.2 days vs. 7.8 ± 2.1 days, p < 0.001), postoperative pain (VAS score 3.2 ± 1.1 vs. 6.5 ± 1.4, p < 0.001), and improved cosmetic outcomes (score 8.5 ± 1.0 vs. 5.5 ± 1.3, p < 0.001) compared to open surgery. The ANOVA analysis further confirmed significant differences between laparoscopic surgery, open surgery, and the control group (p < 0.001) for all three outcomes. These findings support laparoscopy's superiority in terms of patient recovery and quality of life, establishing it as a preferred surgical approach for many gynecological conditions. The study underscores the importance of laparoscopy in advancing gynecological surgery, emphasizing its role in improving surgical outcomes and patient satisfaction.